2012
DOI: 10.2319/111411-705.1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of TAD-anchored maxillary protraction in late mixed dentition

Abstract: Objective: To evaluate the effectiveness of temporary anchorage device (TAD)-anchored maxillary protraction (MP) in terms of the skeletal and dentoalveolar changes and to compare it with traditional tooth-anchored MP. Materials and Methods: A computerized literature search for relative randomized controlled trials and prospective controlled trials was performed in PubMed, MEDLINE, Cochrane Central Register of Controlled Trials, Embase, CNKI, and Google Scholar, complemented with manual search. Data extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…The use of surgical plates has eliminated the need for the cumbersome part-time extra-oral headgear appliance, and the protraction is maintained full-time. A recent systematic review suggested that maxillary protraction anchored with a bone-anchorage device induces more maxillary advancement with minimal dental side effects when compared with tooth-anchored appliances [ 17 ]. Although efficient protraction of the maxilla has been confirmed following the use of surgical plates coupled with intermaxillary Class III elastics, their insertion is undertaken under general anesthesia, unlike temporary anchorage devices (TADs), which are usually placed under local anesthesia [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of surgical plates has eliminated the need for the cumbersome part-time extra-oral headgear appliance, and the protraction is maintained full-time. A recent systematic review suggested that maxillary protraction anchored with a bone-anchorage device induces more maxillary advancement with minimal dental side effects when compared with tooth-anchored appliances [ 17 ]. Although efficient protraction of the maxilla has been confirmed following the use of surgical plates coupled with intermaxillary Class III elastics, their insertion is undertaken under general anesthesia, unlike temporary anchorage devices (TADs), which are usually placed under local anesthesia [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…AMSTAR ratings for the reviews are summarized in Table 2 . [2 , 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26] All 23 reviews were classified as high, medium, or low quality based on 11 domains. Following our previous classification criteria, a grade of 0 to 3 was considered low quality, 4 to 7 was considered medium quality, and 8 to 11 was considered high quality.…”
Section: Resultsmentioning
confidence: 99%
“…This would indicate that there is no clear evidence that skeletal anchorage gives better results than traditional treatments. However, the systematic reviews by Feng et al [28] and Jamilian et al [29] found that maxillary protraction with skeletal anchorage has a greater maxillary advancement effect and seems to reduce some side effects such as mandibular rotation, extrusion of the lower molars or proclination of the upper incisors. The lower incidence of adverse effects is found again in the systematic review by Sahin et al [30], who also concluded that skeletal effects are achieved more rapidly with this type of anchorage.…”
Section: Discussionmentioning
confidence: 99%